Validation of SRS MapCHECK for CyberKnife patient-specific quality assurance: challenges with small cone sizes - Yoo, Dohyeon; Kim, Taeho; Kim, Hojae; Lee, Sangmin; Kim, Dong Wook; Kim, Jin Sung; Lee, Ho; Kim, Hojin (Frontiers in Oncology, 2026)
PurposeThe CyberKnife system, designed for stereotactic radiosurgery (SRS) and stereotactic body radiotherapy (SBRT), considers SRS MapCHECK an effective tool for patient-specific QA (PSQA). This work evaluates the performance of SRS MapCHECK in CyberKnife PSQA, identifies potential sources of inaccuracy in PSQA analysis, and recommends accurate and reliable use of this tool for small fields.MethodsSRS MapCHECK is a promising tool for CyberKnife PSQA due to its compact size and high-resolution 2D detector. It enhances dosimetry accuracy by incorporating correction factors for field size and gantry angle. To validate its effectiveness, PSQAs were performed on CyberKnife plans with various fixed cone sizes for brain SRS cases. Static field dose delivery was tested by rotating robotic arm angles for different fixed cone sizes under various correction settings to assess the impact of these correction factors on dosimetric accuracy.ResultsFor PSQAs on 12 patient plans, statistically significant negative correlation (spearman correlation ρ = -0.87, p-value < 0.0001) was found between cone size and the absolute dosimetric error. Group analysis confirmed significantly larger under-measurements for small fixed cones (≤12.5 mm; mean difference: -5.66 ± 4.31) compared to large cones (≥15 mm; mean difference: -0.16 ± 0.80; unpaired t-test, p-value = 0.0062). Static dose delivery experiments revealed that these discrepancies were primarily linked to the correction factors used in SRS MapCHECK, which showed limited or negative effects for cones ≤12.5 mm despite stabilizing measurements for larger fixed cones (≥15 mm).ConclusionThis study evaluates the suitability of SRS MapCHECK for PSQA of the CyberKnife system and highlights its limitations. It demonstrates that while SRS MapCHECK is effective for larger fixed cone sizes, it does not ensure dosimetric accuracy for plans involving very small fixed cones.